2020
DOI: 10.4314/ejhs.v30i5.3
|View full text |Cite
|
Sign up to set email alerts
|

How Far Does Highly Active Antiretroviral Treatment Reduce TB Incidence among Children? A Marginal Structural Modeling Analysis, Southwest Ethiopia

Abstract: BACKGROUND: Children younger than 15 years, carry almost 80% of the global burden of HIV/AIDS. HIV worsens the progression of latent TB to active TB disease. Although antiretroviral treatment has shown marked reduction in Tuberculosis incidence, TB continues to occur in Sub-Saharan countries including Ethiopia. The aim of this study was to investigate the impact of HAART on the incidence of tuberculosis among children infected with HIV in Southwest Ethiopia.METHODS: A retrospective cohort study was conducted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
2
1
Order By: Relevance
“…This might be due to the differences in sociodemographic and baseline clinical characteristics of study participants and a failure to screen for TB before initiation of ART because this study included health centers. However, it is lower than the finding of a study conducted in southwest Ethiopia, which reported an incidence of TB of 7.9 per 100 child years [8]. Also, this finding is lower than studies conducted in north Ethiopia and Adama Referral Hospital and Medical College, which reported rates of 4.2 and 6.03 per 100 child years, respectively [9,10].…”
Section: Plos Onecontrasting
confidence: 64%
See 2 more Smart Citations
“…This might be due to the differences in sociodemographic and baseline clinical characteristics of study participants and a failure to screen for TB before initiation of ART because this study included health centers. However, it is lower than the finding of a study conducted in southwest Ethiopia, which reported an incidence of TB of 7.9 per 100 child years [8]. Also, this finding is lower than studies conducted in north Ethiopia and Adama Referral Hospital and Medical College, which reported rates of 4.2 and 6.03 per 100 child years, respectively [9,10].…”
Section: Plos Onecontrasting
confidence: 64%
“…Evidence indicates that antiretroviral therapy has significantly reduced morbidity and mortality among people living with HIV [ 8 ]. However, their poor adherence to ART increased the risk of mortality and developing TB by 5.2 and 4-fold, respectively [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation